Emotions and Behaviors of Children Aged 0-6 during the Period of Epidemic Prevention at Home - Xuechang HE; Hui OUYANG; Hanzhang GUO; Zhuoming CHEN; Longbin SHEN; Jianlin OU (康复学报)
Objective:To understand the emotion, behavior and the influencing factors at home epidemic prevention during the epidemic of Corona Virus Disease 2019(COVID-19) in children aged 0-6, and to provide a theoretical basis for the health promotion and family intervention education of that age in similar situations.Methods:On February 24, 2020, a convenient sampling method was used to invite guardians of children aged 0-6 to conduct a online questionnaire survey one month after the government adopted a large-scale outbreak control strategy.Results:The effective rate of the questionnaire was 98.79%(163/165), mainly from Guangdong Province (75.46%). The 9.82%of children experienced mood swings. The only child [χ2=8.82, P=0.003, OR=11.10(2.27-54.40) ] and increased screen time [χ2=8.79, P=0.003, OR=5.80(1.81-18.53) ] were independent risk factor for children's mood swings. The high the father's educational level [χ2=6.17, P=0.013, OR=3.58(1.31-9.81) ], the high family's annual income [χ2=4.52, P=0.033, OR=3.01(1.09-8.31) ] and the reduced frequency of going out [χ2=5.29, P=0.021, OR=4.10(1.23-13.67) ] were independent risk factors for the increase of screen time in children during the epidemic. The increased risk of screen time in children aged (4, 5] was 11.83 times that of children aged (0, 1] (P=0.037), and the increased risk of screen time in children aged (5, 6] was 9.22 times that of children aged (0, 1] (P=0.048). The frequency of adverse emotions was negatively correlated with appetite (P=0.020) and positively correlated to the time spent adapting to home life (P=0.029). The frequency of children living in rural areas going out was significantly higher than that in urban areas (P=0.001). The higher the education level of the father (P=0.003) and mother (P=0.003) were the protective factors for the increase of learning time in children during the epidemic.Conclusion:The only child in the family and the increasing screen time are independent risk factors for children's emotional fluctuations. It will also be accompanied by changes in appetite and decreased ability to adapt. And higher educational level of the father, higher family income, older age, and decreased frequency of outdoors are independent risk factors during the epidemic.